(untitled) - Dougls A Skoog (Philadelphia, Pennsylvania, 1998)
This book is divided into six major sections. *) Section I presents electronic circuit fundamentals, operational amplifiers, digital electronics and computers, signals, noise, data enhancement techniques, and figures of merit. *) Section II provides various branches atomic spectroscopy, including optical absortion, optical emission, and optical fluorescence spectrometry, atomic mass spectrometry, and atomic X-ray spectrometry. *) Section III treats molecular spectroscopy. *) Section IV discusses electroanalytical chemistry techniques including potentiometry, coulometry, and voltammetry. *) Section V presnets various types of chromatography and electrophoresis. *) Section VI discusses miscellaneous instrumental approaches to the solution of analytical problems including thermal, radiochemical, and automated methods
Keywords: instrumental analysis